Forced-Molting methods and their effects on the performance and egg quality of japanese quails (Coturnix japonica) in the second laying cycle - Faitarone, ABG [UNESP] (2008)
The experiment was carried out in the experimental poultry house of the Research and Development Unit of Brotas of Agência Paulista de Tecnologia dos Agronegócios do Centro-Oeste, SP, Brazil. The objective of the study was to evaluate the performance of Japanese quails submitted to forced molting aiming at optimizing the use of the same quail flock by promoting a second laying cycle. A total number of 400 67-day-old Japanese quails in lay, previously submitted to 14 days of forced molting, was distributed in a completely randomized experimental design into five treatments (T1= not submitted to forced molting, T2= 03 days of fasting + fed ad libitum, T3= 01 days of fasting + 13 days of feed restriction, T4= 02 days of fasting + 12 days of feed restriction, and T5= 03 days of fasting + 11 days of feed restriction. Feeds were contained equal nutrient levels, and were formulated according to NRC (1994) recommendations. There were significant differences among the studied treatments. Although the treatment of 3 days of fasting followed by ad libitum feeding resulted in lower egg weight, it promoted better lay percentage, egg mass, and feed conversion ratios (FCR/dz and FCR/kg). on the other hand, 3 days of fasting followed by restricted feeding resulted in higher feed intake and worse feed conversion ratios (FCR/dz and FCR/kg). When birds were not submitted to forced molting, they presented lower lay percentage and egg mass.